Psychopharmacological effects of Artemisia copa aqueous extract in mice - Miño, Jorge Horacio (2010)
Objective: To evaluate the aqueous extract from aerial parts of Artemisia copa Phil. (Asteraceae) administered orallyfor its psychopharmacological activities in several experimental models Methods: The extract was administered p.o. in Swiss albino mice and tested on pentobarbital-induced hypnosis, locomotor activity, exploration in the hole-board, anxiolytic like profile evaluated in the marble-burying test and anticonvulsant activity on convulsions induced by pentylenetetrazol. Results: Artemisia copa at doses up to 1.5g/kg produced a dose-dependent sleep induction and potentiation of sub-hypnotic and hypnotic doses of pentobarbital. The extract also produced a dose-dependent increase and decrease in the spontaneous motor activity (0.51.5g/kg, respectively), no disruption or a decrease on exploratory (hole-board) behavioral profiles (0.51.5g/kg respectively) and a dose-related anxiolytic-like activity as indicated by increases in the percentage of marbles they left uncovered in the marble-burying test at doses (0.5g/kg) that do not disrupt the motor activity. In addition, the extract (1.5g/kg) produced a significant increase in the latency time and a decrease in the duration of seizures and mortality induced by PTZ 75mg/kg in mice. Conclusion: These results suggest that the aqueous extract of Artemisia copa may contain sedative principles with potential anxiolytic and anticonvulsant activities.